Secondary urethral sphincter function of the rabbit pelvic and perineal muscles - Hernandez-Reynoso, Ana G.; Rahman, Farial S.; Hedden, Brian; Castelán, Francisco; Martínez-Gómez, Margarita; Zimmern, Philippe; Romero-Ortega, Mario I. (Frontiers in Neuroscience, 2023)
Perineal and pelvic floor muscles play an important role in continence by providing mechanical support to pelvic organs. It is also known that the pubococcygeus muscle (PcM) contracts in the storage phase and is inactive during voiding, while the bulbospongiosus muscle (BsM) is active during the voiding phase. Recent evidence suggested an additional role of these muscles in supporting urethral closure in rabbits. However, the individual role of perineal and pelvic muscles as urethral sphincters is not well defined. Here we evaluated the individual, sequential and synergistic roles of the PcM and BsM in assisting urethral closure and defined the optimal electrical stimulation parameters that can effectively contract these muscles and increase the urethral pressure (Pura) in young nulliparous animals (n=11). Unilateral stimulation of either the BsM or PcM at 40 Hz induced modest increases in average Pura (0.23±0.10 and 0.07±0.04 mmHg respectively). Investigation on the changes in Pura evoked by stimulation frequencies between 5-60 Hz show that sequential contralateral PcM-BsM activation at 40 Hz induced a two-fold average Pura increase (0.23 ± 0.07 mmHg) compared to that evoked by PcM stimulation. Simultaneous activation of PcM and BsM at 40 Hz also showed an increased average Pura (0.26 ± 0.04 mmHg), with a 2-fold increase in average Pura observed during the unilateral sequential PcM-BsM stimulation at 40 Hz (0.69 ± 0.2 mmHg). Finally, stimulation at 40 Hz of the bulbospongiosus nerve (BsN) induced an approximate 4-fold increase in average Pura (0.87 ± 0.44 mmHg; p<0.04) compared to that elicited by BsM stimulation, confirming that direct nerve stimulation is more effective. Together, this study shows that in the female rabbit, both perineal and pelvic muscles support of the urethral function during continence, and that unilateral stimulation of the BsN at 40-60 Hz is sufficient to achieve maximal secondary sphincter activity. The results also support the potential clinical value of neuromodulation of pelvic and perineal nerves as bioelectronic therapy for stress urinary incontinence.